2015
DOI: 10.1002/ptr.5376
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Tannic Acid on Isoproterenol-Induced Myocardial Injury in Rats: Further Insight into ‘French Paradox’

Abstract: Tannic acid (TA) is a polyphenolic compound, which has shown diverse pharmacological effects with antimutagenic, anticarcinogenic and antibactericidal properties. However, cardioprotective effects of TA have not been reported. To investigate the protective effects of TA, rats were administered TA for 7 days and then intoxicated with isoproterenol (ISO). Myocardial ischemia injury was indicated by changes in electrocardiographic (ECG) patterns, morphology and cardiac marker enzymes. Furthermore, protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…The biochemical blood profile was only slightly affected by TA level. Feeding diets with 2% of TA considerably reduced the activity of CK, a cardiac marker enzyme, which was in agreement with previous findings of cardioprotective effects of TA and other polyphenols [ 4 , 26 , 27 ]. It has recently been suggested that TA maintains the integrity of the cardiac cell membrane and prevents the leakage of CK and other cytosolic enzymes into the bloodstream [ 4 ], which seems to be confirmed by the results of our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The biochemical blood profile was only slightly affected by TA level. Feeding diets with 2% of TA considerably reduced the activity of CK, a cardiac marker enzyme, which was in agreement with previous findings of cardioprotective effects of TA and other polyphenols [ 4 , 26 , 27 ]. It has recently been suggested that TA maintains the integrity of the cardiac cell membrane and prevents the leakage of CK and other cytosolic enzymes into the bloodstream [ 4 ], which seems to be confirmed by the results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Feeding diets with 2% of TA considerably reduced the activity of CK, a cardiac marker enzyme, which was in agreement with previous findings of cardioprotective effects of TA and other polyphenols [ 4 , 26 , 27 ]. It has recently been suggested that TA maintains the integrity of the cardiac cell membrane and prevents the leakage of CK and other cytosolic enzymes into the bloodstream [ 4 ], which seems to be confirmed by the results of our study. TA may exert its cardioprotective effect by reduction of Bax/Bcl-2 ratio, expression of c-fos and c-jun, inhibition of NF-κB activation, as well as due to antioxidative and antiinflammatory properties [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
“…Many antioxidants are supplied by nutrition. A "Mediterranean diet" and moderate wine consumption are thought to have a protective effect ("the French Paradox") due to their high content of antioxidants 56 , 57 . Antioxidants can also be taken as food additives, either as pure compounds, such as vitamins C and E and Q10, or as crude extracts, such as the fermented papaya preparation and curcumin 9 .…”
Section: Oxidative Stressmentioning
confidence: 99%
“…TA has shown various health beneficial activities (Feldman et al, 2001), and many studies have explored its function and biomedical properties, such as anticancer (Feldman et al, 2001), antibacterial (Chung et al, 1998a), antimutagenic, antioxidant (Nakamura et al, 2003), antidiabetic (Liu et al, 2005), antiinflammatory (Lee et al, 2007) and antihypertensive activities (Turgut Cosan et al, 2015). Our recent study showed that TA could exert cardioprotective effects against isoproterenol-induced myocardial ischemia injury in rat heart (Hu et al, 2015). However, no scientific report has systematically demonstrated cellular and ion channel mechanisms of TA in cardiovascular effects.…”
Section: Introductionmentioning
confidence: 99%